2006
DOI: 10.4049/jimmunol.176.9.5671
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Immunization with a Sindbis Virus-DNA Measles Vaccine Induces Adult-Like Neutralizing Antibodies and Cell-Mediated Immunity in the Presence of Maternal Antibodies

Abstract: Infants younger than age 9 mo do not respond reliably to the live attenuated measles vaccine due the immaturity of their immune system and the presence of maternal Abs that interfere with successful immunization. We evaluated the immune responses elicited by Sindbis virus replicon-based DNA vaccines encoding measles virus (MV) hemagglutinin (H, pMSIN-H) or both hemagglutinin and fusion (F, pMSINH-FdU) glycoproteins in neonatal mice born to naive and measles-immune mothers. Despite the presence of high levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 64 publications
(80 reference statements)
2
37
0
2
Order By: Relevance
“…The results described in this study corroborate those reported for other animal species (5,16,21). The superior immunogenicity of pMSIN-H over pMSINHF-dU, for example, has now been confirmed in several animal models.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…The results described in this study corroborate those reported for other animal species (5,16,21). The superior immunogenicity of pMSIN-H over pMSINHF-dU, for example, has now been confirmed in several animal models.…”
supporting
confidence: 90%
“…Both vaccines were highly immunogenic for adult and newborn mice, even in the presence of maternal antibodies (5,15,21). They also elicited high levels of neutralizing antibodies in juvenile and infant rhesus macaques and protected them against respiratory challenge.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Preclinical studies of neonatal DNA vaccination highlight potential advantages of this vector for earlylife immunizations (6). Immunization of neonatal mice with a Sindbis virus DNA measles vaccine induced adult-like neutralizing antibodies and cell-mediated immunity in the presence of maternal antibodies (8). Human adenovirus 5 recombinant viruses expressing the HA and the nucleoprotein of swine influenza virus successfully defeated the suppressive effects of maternal-antibody interference (64), and replication-defective adenovirus expressing rabies glycoproteins in mice resulted in the induction of an endogenous immune response not impaired by maternal immunity (62).…”
Section: Discussionmentioning
confidence: 99%
“…56 Briefly, fecal samples (in 2-fold dilution) were tested in duplicate plates. In one of the plates, 6M urea (Sigma) was added after incubation with samples and incubated for 10 min.…”
Section: Micro-neutralization Testmentioning
confidence: 99%